Study of thermoelectric cooler - Lee, Nicholas Jun (Nanyang Technological University, 2022)
Thermoelectric Coolers (TECs) are fully solid-state heat pump that uses the Peltier effect which transfers heat from one side to the other of the TEC using electric current. Comparing to conventional cooling devices, TECs have the advantages of not having any moving parts and do not involve the use of harmful chlorofluorocarbons as refrigerant. This makes it reliable without any need for maintenance as well as being safe for the environment. However, research has proven that TECs are inefficient to replace conventional cooling devices for large scale cooling due to their lower Coefficient of Performance (COP).